Simulation Approaches To Thermal Comfort In Tvet Workshops: A Review - Norarziana Sasudian; Asmat Ismail; Iryani Abdul Halim Choo (Tech-E, 2026)
Thermal comfort is a crucial element of indoor environmental quality (IEQ), affecting health, cognitive performance, and educational results. Technical and Vocational Education and Training (TVET) workshops exhibit unique thermal issues owing to heat-producing equipment, elevated occupant activity, and intricate ventilation systems. This study consolidates simulation-based studies published from 2016 to 2025 regarding thermal comfort in educational and vocational settings. This narrative review examines the uses of Computational Fluid Dynamics (CFD), EnergyPlus, DesignBuilder, and TRNSYS. The findings indicate that while simulation tools are extensively utilized in classrooms and laboratories, their application in TVET workshops is still constrained. Some of the most important shortcomings are that equipment heat loads are too accessible, occupant activity is not extensively represented, field validation is not effective enough, and hot and humid climates are not given enough attention. The paper supports representative TVET workshop models, hybrid simulation–measurement workflows, and Education 5.0-aligned simulation technologies in vocational education.